Analysis of the Dynamic Response in Blast-Loaded CFRP-Strengthened Metallic Beams - Zhenyu Wang; Yang Zhao; Xu Liang; Zhiguo He (Advances in Materials Science and Engineering)
Carbon fiber-reinforced polymer composites (CFRPs) are good candidates in enhancing the blast resistant performance of vulnerable public buildings and in reinforcing old buildings. The use of CFRP in retrofitting and strengthening applications is traditionally associated with concrete structures. Nevertheless, more recently, there has been a remarkable aspiration in strengthening metallic structures and components using CFRP. This paper presents a relatively simple analytical solution for the deformation and ultimate strength calculation of hybrid metal-CFRP beams when subjected to pulse loading, with a particular focus on blast loading. The analytical model is based on a full interaction between the metal and the FRP and is capable of producing reasonable results in a dynamic loading scenario. A nonlinear finite element (FE) model is also developed to reveal the full dynamic behavior of the CFRP-epoxy-steel hybrid beam, considering the detailed effects, that is, large strains, high strain rates in metal, and different failure modes of the hybrid beam. Experimental results confirm the analytical and the FE results and show a strong correlation.